Le fonti del diritto al tempo dell’emergenza pandemica. Note su alcune tendenze in atto (Società e diritti, 2021)
AbstractThe article deals with the relationship between the sources of law and the management of pandemic emergency in Italian legal system. This question is part of some current trends regarding the complexity of contemporary law. It works through the articulation of sources of several origins and authoritativeness, in an unstructured, fragmentary, fluid context with a network frame that obscures their hierarchical order. In this scenario, the function of soft law plays an important role. The disorder of the sources is connected to the issues of legal certainty and interpretation.